Organizational Culture, Governance Structure and Sustainability Disclosure Quality: Evidence from Indonesia, Malaysia, Singapore, and Thailand - Shwairef, Abdalla Meftah; Abdulrahim, Mohamed Omar; Sukoharsono, Eko Ganis (Universitas Negeri Semarang, 2021)
Sustainability disclosure has been an interesting topic and issue in this recent decades. This study aims to analyze the mediating effect of organizational culture in the relationship between governance structure and sustainability disclosure quality in four Asian countries: Indonesia, Malaysia, Singapore, and Thailand. The method for collecting data is documentation with secondary data. The data were obtained for the 2015-2019 period from the Indonesian stock exchange, Malaysia stock exchange, Singapore stock exchange, Thailand stock exchange, and other related sources comprising the company’s website. The results showed that the governance structure positively affects organizational culture that consists of clan culture, adhocracy culture, hierarchy culture, and market culture. Meanwhile, the significance values of the variables Board Size, Board Independence, Organizational Culture, Institutional Ownership, and Audit Committee, clan, adhocracy, and hierarchy and marker culture affect the sustainability of disclosure quality. This result indicated that implementing organizational culture and governance structure better will increase sustainability disclosure quality in these four Asian countries. Keywords: Governance Structure; Organizational Culture; Sustainability Disclosure Quality